Toward a transformative climate change adaptation from local to global perspective—A transdisciplinary challenge by Kyoto Climate Change Adaptation Center - Ichihara, Masako; Nakagawa, Yoshinori; Ishii, Reiichiro; Saijo, Tatsuyoshi; Yasunari, Tetsuzo (Frontiers in Climate, 2024)
Policies for climate change adaptation differ from those for climate change mitigation, both of which share the common aim of maintaining a sustainable climate system that enables humankind to survive while enjoying well-being. Considering the variability in regional conditions, they must be diverse throughout the policymaking process, with the participation of multiple stakeholders, to place the livelihood of residents as the central issue. Simultaneously, these regional diversities must also be realized in a manner consistent with the global goal of climate change mitigation. To that end, comprehensive and transformative adaptation measures are essential, rather than responding to imminent issues on an ad hoc basis. As the literature shows, a transdisciplinary approach involving researchers across different fields and multiple non-academic sectors can fill the gaps in transformative adaptation. Still, it has yet to be implemented because of the lack of experience of this issue. Here, we present key findings that affect the generation of synergies and tradeoffs among issues through our novel transdisciplinary approach in Kyoto, Japan, via a series of Future Design workshops in agriculture in collaboration with local farmers, regional policymakers, and researchers with diverse backgrounds. These results provide a direction for future research to secure a methodological foundation that will facilitate the sustainability of these efforts.